Depredación en la tortuga carey Eretmochelys imbricata por el Jaguar Panthera onca en la costa del Pacífico de Costa Rica - Hansel Herrera; Sergio Escobar-Lasso; Eduardo Carrillo-Jiménez (Mammalogy Notes, 2016)
In the sea, the most common predators of adult sea turtles are sharks (i.e., Carcharhinus leucas, Carcharodon carcharias, Galeocerdo cuvier) (Witzell 1987, Cliff & Dudley 1991, Fergusson et al. 2000) and killer whales (Orcinus orca) (Fertl & Fulling 2007); while on their nesting beaches, female turtles are susceptible to predators like jaguars (Panthera onca) and crocodiles (Crocodylus acutus) (Ortiz et al. 1997, Heithaus et al. 2008).